IRON-DEFICIENCY ANEMIA: HEALTHY NUTRITION AND DETECTION METHODS - U.Khatamova (Prospects for innovative technologies in science and education, 2026)
Iron-deficiency anemia (IDA) is the most common nutritional disorder worldwide, characterized by reduced hemoglobin levels and insufficient red blood cell production due to inadequate iron availability. IDA can lead to fatigue, cognitive impairment, and reduced immunity. This article reviews dietary strategies for prevention and management of IDA, as well as methods for early detection and monitoring, highlighting the importance of a balanced diet and regular medical evaluation.